2020
DOI: 10.3390/met10111412
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependent Solid Solution Strengthening in the High Entropy Alloy CrMnFeCoNi in Single Crystalline State

Abstract: The main difference between high entropy alloys and conventional alloys is the solid solution strengthening effect, which shifts from a single element to a multi-element matrix. Little is known about the effectiveness of this effect at high temperatures. Face-centered cubic, equiatomic, and single crystalline high entropy alloy CrMnFeCoNi was pre-alloyed by arc-melting and cast as a single crystal using the Bridgman process. Mechanical characterization by creep testing were performed at temperatures of 700, 98… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 41 publications
1
6
0
1
Order By: Relevance
“…The MPEA has extraordinary mechanical properties, including the excellent creep resistance, which plays an important role in engineering application at room temperature and low stress, owing to strong diffusion resistance caused by the lattice distortion arising from the difference in atomic sizes (Kang et al, 2018;Tsai et al, 2018;. The CrMnFeCoNi MPEA exhibits excellent creep resistance compared to nickel base alloys as shown in Figure 4 (Gadelmeier et al, 2020). The high creep resistance of CoCrFeMnNi at intermediate temperatures (0.2-0.6 Tm where Tm is the melting temperature) is attributed to the solution strengthening from the large atomic-size misfit of Cr (Kang et al, 2018).…”
Section: Creep Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…The MPEA has extraordinary mechanical properties, including the excellent creep resistance, which plays an important role in engineering application at room temperature and low stress, owing to strong diffusion resistance caused by the lattice distortion arising from the difference in atomic sizes (Kang et al, 2018;Tsai et al, 2018;. The CrMnFeCoNi MPEA exhibits excellent creep resistance compared to nickel base alloys as shown in Figure 4 (Gadelmeier et al, 2020). The high creep resistance of CoCrFeMnNi at intermediate temperatures (0.2-0.6 Tm where Tm is the melting temperature) is attributed to the solution strengthening from the large atomic-size misfit of Cr (Kang et al, 2018).…”
Section: Creep Resistancementioning
confidence: 99%
“…FIGURE 4 |The log-log of minimum creep rate vs. stress of the CrMnFeCoNi MPEA compared with pure nickel at different temperature(Gadelmeier et al, 2020).…”
mentioning
confidence: 99%
“…Існують високоентропійні сплави із структурою на основі твердих розчинів, суміші інтерметаллідних фаз, аморфних фаз, а також сплави із складною багатофазною структурою. [1][2][3][4][5][6][7]. Завдяки високій твердості та зносостійкості, стійкості до іонізуючих випромінювань, антибактеріальним властивостям та корозійній стійкості, високоентропійні сплави є перспективними матеріалами для різних галузей техніки [8][9][10][11][12][13][14][15][16][17].…”
Section: вступunclassified
“…High-entropy alloys are cutting-edge materials with complex compositions and unusual properties as compared to conventional alloys. Gadelmeier et al [1] studied the creep behavior of a single crystal high-entropy CrMnFeCoNi alloy in comparison with single crystal pure nickel. This research revealed the effect of the solid solution strengthening and dislocation strengthening in the absence of grain boundaries on the creep strength at high temperatures (700-1200 • C).…”
Section: High-entropy Alloysmentioning
confidence: 99%